Transmutation of Sweat Glands - Eccrine Porocarcinoma - Anubha, Bajaj (Journal of Clinical and Diagnostic Pathology, 2019)
Initially described by Pinkus and Mehregan in 1963 as an  epidermotropic eccrine carcinoma, eccrine porocarcinoma cogitates an exceptional sweat gland malignancy. Eccrine porocarcinoma was adapted as a nomenclature by Mishisma and Morikoin in 1969. The neoplasm is a malignant analogue of eccrine poroma which is a benign tumour of intra-dermal sweat glands. Eccrine porocarcinoma  is an invasive malignancy of eccrine sweat gland with an acrosyringial genesis. Nomenclature includes epidermotropic eccrine carcinoma, eccrine poroepithelioma, malignant  hidroacanthoma simplex, malignant intra-epidermal eccrine poroma, malignant eccrine poroma, malignant syringoacanthoma and dysplastic poroma (1,2). Sweat gland carcinoma are categorized into subgroups with the classical eccrine porocarcinoma  or  eccrine adenocarcinoma as a prevalent subcategory. Lesions are enlisted as          Classic type eccrine adenocarcinoma ( eccrine porocarcinoma). Syringoid eccrine carcinoma                                                                                   Microcystic adnexal carcinoma                                                                 Mucinous eccrine carcinoma                                                           Muco-epidermoid carcinoma                                                                           Adenoid cystic carcinoma                                                                         Aggressive digital papillary adenoma/adenocarcinoma
Keywords: Mucinous eccrine carcinoma; Adenoid cystic carcinoma